Statistical benchmarking of voting theory methods - Krylovas, Aleksandras; Kosareva, Natalja (Lietuvos matematikos rinkinys, 2016)
In the article 8 candidates sorting algorithms were compared by Monte Carlo experiments. 6 of them are constructed on the basis of voting theory and 2 – on the basis of Kemeny median. The largest number of correct decisions averages and the least average number of unfinished voting procedures were shown by the median-based sorting algorithms.